Evaluation of polymorphisms in the MBL2 gene exon 1 and their relevance to susceptibility to bovine papillomatosis in Girolando breed animals - Pessoa Junior, Morse Edson; Carrazzoni, Patrícia Gallindo; Tenório Filho, Fernando; Alves, Ryan Vieira; Freitas, Antonio Carlos de; Silva, Maria Angélica Ramos da (Revista Principia, 2025)
Bovine papillomatosis is an infectious viral disease caused by Bovine Papillomavirus (BPV). Single-nucleotide polymorphisms (SNPs) in genes associated with innate immunity have been widely investigated due to their relevance to animal disease susceptibility. Mannose-binding lectins (MBLs) are critical components of the innate immune response against various infectious agents, including viruses. Polymorphisms in the MBL2 gene may influence protein functionality, and this study aimed to evaluate the association between polymorphisms in exon 1 of the MBL2 gene and susceptibility to bovine papillomatosis. Blood samples were collected from 167 Girolando cattle (Gir × Holstein) from Northeastern Brazil, all carriers of BPV. Among these, 92 animals presented cutaneous symptoms of the disease, while 75 were asymptomatic. DNA was extracted from the samples, followed by PCR to detect BPV and polymorphisms, sequencing, and sequence alignment. SNPs were analyzed using SNPStats software, with a significance threshold set at 5%. The association between polymorphisms in exon 1 of the MBL2 gene and the development of papillomatosis was assessed using the Odds Ratio test, with a 95% confidence interval. Sequence analysis revealed 245 conserved sites and two variable sites, G235A and T244C, in exon 1 of the MBL2 gene. However, no significant association was identified between these SNPs' allele and genotype frequencies and susceptibility to cutaneous papillomatosis.